El momento actual Español, cargado de utopía / M° Teresa de Borbón-Parma ; [prólogo José Luis L. Aranguren] - Borbón Parma, María Teresa de (1933-) (Divulgación universitaria; 119. Cuestiones Españolas)
Bibliografía: p. 185-186